Pengaruh Kualitas Pelayanan Proses Penyusunan Skripsi Dan Keaktifan Mahasiswa Terhadap Tingkat Kepuasan Mahasiswa Pada Program Studi Pendidikan Akuntansi Fakultas Keguruan Dan Ilmu Pendidikan Universitas Muhammadiyah Surakarta Angkatan 2012 - Rusmeti, Atina, Drs. Djumali, M.Pd (2016)
This study aims to determine: 1) The effect of service quality thesis preparation process to the level of student satisfaction; 2) The effect of the activity of students to the level of student satisfaction; 3) The impact of service quality thesis preparation process and activity students on the level of student satisfaction This type of research is descriptive quantitative research. This study took place in the Campus of the Faculty of Teacher Training and Education Program Accounting Education Muhammadiyah University of Surakarta. The population in this study is the Faculty of Teacher Training and Education Program of Accounting Studies University of Muhammadiyah Surakarta Force 2012 which amounted to 129 students taking thesis. Samples taken as many as 95 students with incidental sampling technique. The technique of collecting data using questionnaires and documentation. Data analysis technique used is multiple linear regression analysis, t-test, F, R2 test, the relative contribution and effective contribution. The regression results obtained by the regression equation Y = 1.997 + 0,601X1 + 0,347X2. The conclusion of this study are: 1) Quality of thesis preparation process positive and significant impact on the level of student satisfaction. Based on t test obtained t> t table is 5.923> 1.986 and the significance probability value <0.05, namely 0.000. 2) The active participation of students positive and significant effect on the level of student satisfaction. Based on t test obtained t> t table is 3.827> 1.986 and the significance probability value <0.05, namely 0.000. 3) Quality of thesis preparation process and activity of students together positive and significant impact on the level of student satisfaction. Based on F test obtained F count> Ftable is 147.851> 3.095 and the significance probability value <0.05, namely 0.000. 4) The variable quality of service thesis preparation process gives the relative contribution of 85.1% while the variable activity of students leave the relative contribution of 2.2%. 5) The variable quality of the process of preparation of the thesis service contribute effectively 72.5%. Variable liveliness students contribute effectively 3.8%, bringing the total effective contribution of both variables 76,3%, while the remaining 23.7% is influenced by other variables not examined.